Synopsis 3 : testimonies : between fiction & reality - National Museum of Contemporary Art, Athens; Kafetsi, Anna (Athene : EMST (National Museum of Contemporary Art) Athens, 2003)
Ataman, Kutlug ; Charalambides, Nikos ; Geers, Kendell ; Grimonprez, Johan ; Kentridge, William ; Ra'ad, Walid ; Salloum, Jayce ; Sekula, Allan ; Sidén, Ann-Sofi ; Tan, Fiona ; The Atlas Group ; Theodorou, Lina ; Wearing, Gillian ; Yan Pei-Ming
biog., tent., bibliog. p. 257-263
Engels
Grieks
Publication on the occasion of the exhibition Synopsis 3 : Testimonies : between fiction & reality in EMST (National Museum of Contemporary Art) in Athens, 10.12.2003-29.02.2004
boek